Transition States of Telecommunication Network - Andrej Sulovec; Gustav Cepciansky (Advances in Electrical and Electronic Engineering, 2004)
The dimensioning and performance of the telecommunication network take place according to the theory of teletrafficalways taking into account the stable state. But the utterance of the network being in an unstable state is less known. In this paper, wewould like to remind the network performance in the unstable state and to draw attention to the practical consequences of transitionstates.